Determination of Normal Hydrocarbons C5-C18 Using Silanized Algerian Bentonite (B1100) as Support in Gas Chromatographic Analysis - LAHMEK, M.; RAMADAN, A.A. (Asian Journal of Chemistry, 2010)
A support was prepared from Algerian Bentonite by thermal treatment at 1100 ºC and chemically by 6N HCl to remove the soluble metallic oxides especially iron oxide until we obtained white granules with diameter range 125-150 μm. The support specific surface area was measured to be 12 m2/g. The support granules were silanized with dimethylchlorosilane (DMCS) at 120 ºC in the vapour phase. Determination of different mixtures of normal hydrocarbons C5 to C18 using silanized Algerian Bentonite (B1100) as support in gas chromatographic analysis gives high accurate and sensitive results. In all separations of mixtures using columns (200 cm × 2 mm), packed with modified Bentonite, the separated peaks with relative standard deviation not exceeding 3.1% were obtained.